Design and Investigation of Characteristic Structure Split Ring Resonator Circular of Microwave Metamaterial Absorber Parameter in X-band Frequency - Fahmi, Arif; Setijadi, Eko; Handayani, Puji (IPTEK Journal of Proceedings Series, 2019)
This paper explained the design and investigation of the characteristic structure of split ring resonator circular in the parameter of microwave metamaterial absorber in X-band frequency. The result showed that bigger value of inner radius circular geometry obtained the resonance frequency shifted to bigger such as 9.20 GHz to 9.30 GHz, and maximum absorption rate increased from 88.9% to 93,35%. When the inner radius smaller and the outer higher, represented the resonance frequency shifted to lower, 11.13 GHz to 9.94 GHz, and the maximum absorption rate decreased from 85% to 78,27%. In another condition, the lower gap variation affected resonance frequency shifted to lower 9.30 GHz to 9.13 GHz but maximum absorption rate increased 88.64% to 89,2%, thus opposite.